Study of Sericite Quartz Schist Coarse-Grained Soil by Large-Scale Triaxial Shear Tests - Zhang, Hui-qing; Zhao, Feng; Cheng, Shi-qiang; Zhang, Yan-qing; Gou, Ming-jie; Jing, Hong-jun; Zhi, Hong-feng (Frontiers in Physics, 2020)
The large-scale triaxial consolidated-drained (CD) and consolidated-undrained (CU) shear tests were carried out to investigate performances of the sericite quartz schist coarse-grained soil on stress-strain, deformation, and strength under four different confining pressure conditions. The test results indicated that the stress-strain curve of sericite quartz schist was nonlinearity, compressive hardening and elastic-plastic. The shear strength envelope curve was better. In the triaxial CD shear test, the sericite quartz schist exhibited weak strain softening under different confining pressures. The sample showed shearing shrinkage at first and later dilatancy under confining pressures of 200, 400, and 600 kPa. When the confining pressure was 800 kPa, the sample showed a trend of shearing shrinkage. In the triaxial CU shear test, the sericite quartz schist exhibited strain hardening, presenting a tendency of shearing shrinkage at first and later dilatancy. It is more reasonable to take account of the cohesion of sericite quartz schist in practical engineering design by linear-regression analysis.